Co-workers in the field of souls: the Civil War partnership between Union chaplains and the U.S. Christian Commission, 1861-1865 - Pickard, Scott D. (Kansas State University, 2013)
A religious revival movement occurred in the Union Army during the American Civil War (1861-1865). The revivals began to appear with some regularity at the end of 1862 and continued until the end of the conflict. Union soldiers also widely adopted Protestant evangelical values during this time of religious enthusiasm. Two groups in particular played a pivotal, yet often unheralded, role in the substantial growth of religious fervor among northern soldiers during the Civil War: Union military chaplains and the United States Christian Commission. The thesis of this work is that Union chaplains and the United States Christian Commission developed a close and effective wartime partnership that significantly facilitated their ability to promote Protestant evangelical Christianity among Union soldiers during the Civil War. This wartime association substantially aided their efforts to advance their theological and moral views among the troops. Union chaplains and Commission representatives gained considerable influence over the army’s spiritual and moral environment during the war and were primarily responsible for initiating the widespread revivals that occurred within the Union Army. Although they began the conflict as two distinct organizations, Union chaplains and the Christian Commission collaborated with increasing frequency as the war progressed. Their affiliation brought a number of advantages to each organization and significantly increased their ability to promote their evangelical beliefs with the soldiers. This dissertation contributes to studies on religion and the Civil War by analyzing the religious leadership provided by Union chaplains and the Christian Commission and explains how they shaped the Union Army’s religious environment during the war.
Keywords: Religion and the American Civil War; Union chaplains; United States Christian Commission; History (0578)